Community Service: Education to the Fishermen Community of Bagan Deli Village on How to Build an E-Commerce Website with Google Site - Pasaribu, Sutrisno Arianto; Rozi, Ahmad; Marpaung, Preddy; Amalia, Suci; Reivan, M; Sati, Fadya Lara (Jurnal Pengabdian Pancasila (JPP), 2024)
The Community Service Program in Bagan Deli Village focuses on educating fishermen about creating e-commerce websites using Google Sites. This initiative aims to increase community awareness of the importance of technology in improving access to information, supporting education, and improving living standards. Training and mentoring are conducted to empower the community to understand the basics of website development, which is expected to improve their economy. The program also encourages the provision of scholarships and regular education for local people, reduces unemployment, and strengthens the independence of fishing communities through technology and education.